Analysis of The Reba Method of Work Posture on Reducing Musculoskeletal Disorders (MSDs) in Nurses at Aisyiyah Hospital - Nuirhaida Nuirhaida; Fluorin Oryza Muslim; Astrina Aulia; Silvia Nengcy (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
According to the World Health Organization (WHO), musculoskeletal disorders (MSD’s) include conditions that affect muscles, joints, bones, and other supporting tissues and can cause pain and limited movement. Based on the report of the Indonesian Ministry of Health in 2020, approximately 16% of workplace diseases are caused by musculoskeletal diseases. This study aims to determine the relationship between nurses' work posture (REBA assessment results) and nurse demographic factors with the incidence of Musculoskeletal Disorders. This study is quantitative with a cross-sectional method with a population of 30 people with a total sampling technique on all nurses. When conducting REBA observations, interviews and questionnaires were used to obtain primary data. From the results of the study, the variables that influence reducing MSD’s are education with a P-value of 0.03. For the REBA method, which is a technique for assessing body posture at work, age, BMI, and length of service do not affect MSD’s. Education can provide knowledge about ergonomics so that nurses can overcome MSD complaints by carrying out work with a good working posture that can reduce MSD complaints that are not high on the pain scale.